Identifikasi Keragaman Plasma Nutfah Bunga Telang (Clitoria ternatea L.) Di Provinsi Maluku Utara - Surisno. M. Hi. Husen; Sri Soenarsih; Shubzan A. Mahmud (Jurnal Pertanian Khairun, 2023)
The Clitoria ternatea plant which has the common name flower telang is a perennial shrub that has deep and woody roots, slightly upward or upright and climbing stems with a height between 20 - 90 cm, downy hair, three to five leaves, oval leaflets the upper surface is hairless and the lower surface is scattered with hairs, flowering bunches in the armpits with 1-2 flowers, the length of the petiole is up to 4 cm, the petals are purple to almost white, the pods are spun oval, hairless, seeds 3-7 , convex valve, seeds round to ovate, brownish in color. The research objective was to determine the diversity of clitoria ternatea flower plants in North Maluku province and as a breeding material for the development of telang flower plants. This research uses descriptive method with direct observation techniques on the object being observed. Morphological and agronomic character data were obtained through surveys and direct observation of sample plants in the field based on modified telang plant descriptor guidelines (IBPGR, 1983 and e-Floras, 2010). From the research found 14 accessions of Clitoria ternatea in North Maluku Province and showed diversity in leaf color, leaf length, leaf length, leaf width, leaf blade size, leaf shape, leaf stalk length, protective crown size, pod length, pod width. pod color, degree of pod curvature, shape of pod beak curvature, seed color, seed coat glossy, number of seeds / pods, maximum number of ovules / pods, weight of seeds / seeds, weight of seeds / pods. The kinship relationship of 14 accessions, cluster I level of similarity 50.55%, cluster II 60.75% and cluster III 42.31%.Keywords: Telang Flower, Germplasm, Diversity